Impacts of Bisphenol A and Ethinyl Estradiol on Male and Female CD-1 Mouse Spleen - Robin B. Gear (Nature Portfolio, 2017)
Abstract The endocrine disruptor bisphenol A (BPA) and the pharmaceutical 17α-ethinyl estradiol (EE) are synthetic chemicals with estrogen-like activities. Despite ubiquitous human exposure to BPA, and the wide-spread clinical use of EE as oral contraceptive adjuvant, the impact of these estrogenic endocrine disrupting chemicals (EDCs) on the immune system is unclear. Here we report results of in vivo dose response studies that analyzed the histology and microstructural changes in the spleen of adult male and female CD-1 mice exposed to 4 to 40,000 μg/kg/day BPA or 0.02 to 2 μg/kg/day EE from conception until 12–14 weeks of age. Results of that analysis indicate that both BPA and EE have dose- and sex-specific impacts on the cellular and microanatomical structures of the spleens that reveal minor alterations in immunomodulatory and hematopoietic functions. These findings support previous studies demonstrating the murine immune system as a sensitive target for estrogens, and that oral exposures to BPA and EE can have estrogen-like immunomodulatory affects in both sexes.